Numerical Techniques for Methane Modeling During the Warm-Up of Converters - Chauhan, Sanchita (Asian Journal of Chemistry, 2010)
Numerical simulation is carried out for reducing the concentration of polluting methane during the warm-up period of the converter. A comparison between two numerical techniques namely the quasi steady state model (QSSM) and the unsteady state model (USSM) was carried out.